The use of whole-genome sequencing and development of bioinformatics to monitor overlapping outbreaks of Candida auris in southern Nevada - Gorzalski, Andrew; Ambrosio, Frank J.; Massic, Lauryn; Scribner, Michelle R.; Siao, Danielle Denise; Hua, Chi; Dykema, Phillip; Schneider, Emily; Njoku, Chidinma; Libuit, Kevin; Sevinsky, Joel R.; Van Hooser, Stephanie; et al. (Frontiers in Public Health, 2023)
A Candida auris outbreak has been ongoing in Southern Nevada since August 2021. In this manuscript we describe the sequencing of over 200 C. auris isolates from patients at several facilities. Genetically distinct subgroups of C. auris were detected from Clade I (3 distinct lineages) and III (1 lineage). Open-source bioinformatic tools were developed and implemented to aid in the epidemiological investigation. The work herein compares three methods for C. auris whole genome analysis: Nullarbor, MycoSNP and a new pipeline TheiaEuk. We also describe a novel analysis method focused on elucidating phylogenetic linkages between isolates within an ongoing outbreak. Moreover, this study places the ongoing outbreaks in a global context utilizing existing sequences provided worldwide. Lastly, we describe how the generated results were communicated to the epidemiologists and infection control to generate public health interventions.